Reactions and Biological Activities of Hydrazonoyl Halides - Alarbash, Munirah F; Al-Faiyz, Yasair S; Wiggins, Jeffrey S; Sayed, Abdelwahed R (Current organic synthesis, 2024)
This review covers the literature information on the chemistry of hydrazonoyl halides with different substrates to give heterocyclic compounds. From the foregoing survey, it seems this provides a useful and convenient strategy for the synthesis of numerous heterocyclic derivatives. The subject of such reactions is still ongoing and undoubtedly will provide new fused functionalized compounds of both industrial and biological interest. A literature survey revealed that a great deal of interest has been focused on the synthesis of functionalized heterocyclic compounds due to their wide range of biological activities, such as contact dermatitis, anthelmintic, antiviral, antimicrobial, herbicidal, and anti-cancer. On the other hand, hydrazonoyl halides are interesting synthons for valuable bioactive heterocyclic compounds. The reaction of hydrazonoyl halides with various types of substrates gave a huge number of different heterocyclic systems. In this review, we collected all reactions of hydrazonoyl halides with different moieties and classified them as aryl diazo of monoheterocycles, aryldiazo of 5,5-bis-heterocycles, aryldiazo of 5,6-bis-heterocycles, aryldiazo of 6,6-bis-heterocycles, aryldiazo of 5,5,6-tri-heterocycles, aryldiazo of 5,6,6-tri-heterocycles, aryldiazo of 6,6,6-tri-heterocycles, hetero annulation of bisheterocycles, hetero annulation of tri-heterocycles, hetero-annulation of tetra-heterocycles, synthesis of spiro-heterocycles, heterocyclic ring transformations, and 1,3-dipolar cycloaddition reactions catalyzed by transition metals using hydrazonoyl halides as substrates.Most reaction types have been successfully applied and used in the production of biologically active compounds. The aim of the present survey is to consider in the reader the opportunity interactions and biological activities of hydrazonoyl halides. The information of several artificial paths and varied physics-chemical factors of such heterocycles made a special consideration of chemists in different fields to yield a combinatorial library and carry out thorough efforts in the search for hydrazonoyl halides.